2000
DOI: 10.1046/j.1460-9568.2000.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged cholinergic forebrain neurons and improved spatial learning in p75 knockout mice

Abstract: The p75 low affinity neurotrophin receptor (p75) can induce apoptosis in various neuronal and glial cell types. Because p75 is expressed in the cholinergic neurons of the basal forebrain, p75 knockout mice may be expected to show an increased number of neurons in this region. Previous studies, however, have produced conflicting results, suggesting that genetic background and choice of control mice are critical. To try to clarify the conflicting results from previous reports, we undertook a further study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 41 publications
(83 reference statements)
8
60
2
1
Order By: Relevance
“…Although our analysis did not specifically determine that ChAT-positive cells had died after A␤ 1-42 exposure at axonal terminals, it did demonstrate the loss of cellular neurotransmitter production and hence loss of function of these neurons. It has also been shown in aged animals that ChAT downregulation correlates with loss of hippocampal function (Yeo et al, 1997) and that this precedes the death of basal forebrain neurons (Greferath et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our analysis did not specifically determine that ChAT-positive cells had died after A␤ 1-42 exposure at axonal terminals, it did demonstrate the loss of cellular neurotransmitter production and hence loss of function of these neurons. It has also been shown in aged animals that ChAT downregulation correlates with loss of hippocampal function (Yeo et al, 1997) and that this precedes the death of basal forebrain neurons (Greferath et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To determine cell survival of cholinergic basal forebrain neurons, the rostral half of each brain between Ϫ1.4 and Ϫ0.5 mm from bregma (the medial septum and diagonal band of Broca) was cut by vibratome into 15 60-m-thick serial coronal sections. Floating sections were stained with a rabbit anti-choline acetyltransferase (ChAT) polyclonal antibody (1:500; Ab143; Millipore Bioscience Research Reagents), and all ChAT-positive neurons in the area of interest were counted based on the method of Greferath et al (2000).…”
Section: Methodsmentioning
confidence: 99%
“…p75NTRϪ/Ϫ mice were obtained from a colony previously shown to be 95% congenic to the inbred SVJ-129 strain (Greferath et al, 2000) and subsequently back-crossed a further 12 generations.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic background has long been known to influence the behavioral phenotype of mutant mice (Shanks and Anisman, 1988,Gerlai, 1996,Logue et al, 1997,Bouwknecht and Paylor, 2002,Schauwecker, 2002,McKhann et al, 2003,Sik et al, 2003,Waddell et al, 2004, but fewer studies have focused on the brain-based mechanisms for such strain dependence. Brain (Bilovocky et al, 2003) and limb (Murcia et al, 2004) phenotypes caused by mutation of the Engrailed-1 (en-1) gene are highly dependent upon genetic background, as are the neural phenotypes produced by mutations of p75NGF (Greferath et al, 2000), Unc5c (Burgess et al, 2006), fmr-1 (Paradee et al, 1999,Dobkin et al, 2000,Ivanco and Greenough, 2002,Mineur et al, 2002,Errijgers and Kooy, 2004 and Pax2 (Schwarz et al, 1997). Herrup and colleagues have identified one significant modifier and several other possible loci that may be responsible for trait differences in limb and cerebellum specification in the en-1 knockout (Murcia et al, 2004,Murcia et al, 2006, and a recent report identified a major modifier locus that influences phrenic motor axon guidance in the absence of Unc5c (Burgess et al, 2006).…”
Section: The Influence Of Genetic Background On the Expression Of Phementioning
confidence: 99%